A distinctive new species of wild banana (Musa, Musaceae) from northern Vietnam - Lý, Ngọc-Sâm; Lê, Công-Kiệt; Triệu, Tiến-Dũng; Haevermans, Agathe; Lowry, Porter Ii P.; Haevermans, Thomas (Phytotaxa, 2012)
A new banana species, Musa haekkinenii, is described from northern Vietnam. It differs notably from a well-known ornamental species, M. coccinea, by inflorescence features and leaf blade shape and especially the habit, shape, size and color of the male bracts of the inflorescences and male bud shape. A mixed watercolor and ink plate is provided for the new taxon and an identification key to species of Musa sect. Callimusa is included, along with a note comparing the morphology of the seven Indo-Chinese species.